Robust synchronization of coupled circadian and cell cycle oscillators in single mammalian cells. Issue 7 (15th July 2014) - Bieler, Jonathan; Cannavo, Rosamaria; Gustafson, Kyle; Gobet, Cedric; Gatfield, David; Naef, Felix
Abstract: Circadian cycles and cell cycles are two fundamental periodic processes with a period in the range of 1 day. Consequently, coupling between such cycles can lead to synchronization. Here, we estimated the mutual interactions between the two oscillators by time‐lapse imaging of single mammalian NIH3T3 fibroblasts during several days. The analysis of thousands of circadian cycles in dividing cells clearly indicated that both oscillators tick in a 1:1 mode‐locked state, with cell divisions occurring tightly 5 h before the peak in circadian Rev‐Erb α‐YFP reporter expression. In principle, such synchrony may be caused by either unidirectional or bidirectional coupling. While gating of cell division by the circadian cycle has been most studied, our data combined with stochastic modeling unambiguously show that the reverse coupling is predominant in NIH3T3 cells. Moreover, temperature, genetic, and pharmacological perturbations showed that the two interacting cellular oscillators adopt a synchronized state that is highly robust over a wide range of parameters. These findings have implications for circadian function in proliferative tissues, including epidermis, immune cells, and cancer. Synopsis: Single‐cell time‐lapse analyses in mouse cells show that circadian and cell cycles are robustly synchronized. This state reflects a predominant unilateral influence of the cell cycle on the circadian oscillator. Circadian and cell cycles in mouse NIH3T3 cells proceed in tight synchrony that is highly robust over a wide range of conditions. The synchronized state reflects predominant influence of the cell cycle on the circadian cycle. Timing of divisions relative to the circadian cycle is predicted by the period mismatch of the two cycles. Stochastic modeling of two interacting phase oscillators identifies the parameters of the coupling functions. Abstract : Single‐cell time‐lapse analyses in mouse cells show that circadian and cell cycles are robustly synchronized. This state reflects a predominant unilateral influence of the cell cycle on the circadian oscillator.